Konfliktusmenedzsment az elméletben és gyakorlatban Thomas Kilman modellje alapján - Benke, Mariann (Közép-Európai Közlemények, 2024)
The paper aims to examine conflict management opportunities in teams with the conflict model of Thomas and Kilmann1. This examination is confirmative research about the model and the questionnaire which tries to test the validity of this methodology. The first important goal of the research is to simulate a conflict situation where the participants must solve the conflict, before the simulation the participants (mostly students) fill in a questionnaire. The study compares the results of the questionnaire with the real behavior and assumption of the participants during a special decisionmaking business game2. The number of participants was 286 who answered the modified conflict management questionnaire and take part in the conflict management simulation from 2018 until 2023. 50 participants participated only in the conflict management game in 2018 it was the first part of the research. There were 13 participants from the Hungarian division of a multinational company – who completed only the conflict management questionnaire – and the other participants were students from Hungary, the Check Republic, the United States, and other international students from different parts of the world. The most important result of the research is that the behavior of the participants could be different during a real conflict situation from the results of the questionnaire showed.